The effect of exercise training as adjuvant treatment on mean pulmonary arterial pressure by echocardiography and functional capacity in congenital heart disease with negative vaso reactivity test pulmonary hypertension patient at Saiful Anwar Hospital Malang - Firdaus, Muhammad; Heny Martini; Wella Karolina; Valerinna Yogibuana; Cholid Tri Tjahjono (Universitas Brawijaya, 2025)
Background : PH is defined by mPAP >20 mmHg at rest. Exercise training enhances hemodynamics and exercise capacity in PH patients. Echocardiography is essential for assessing and evaluating PAP in PH cases. Objective : This study aims to determine the effect of 12-weel exercise training on mPAP by echocardiography and functional capacity Methods : A prospective cohort study at Saiful Anwar General Hospital (Sept 2024-Jan 2025) investigated exercise effects on mPAP and functional capacity in pulmonary hypertension patients. Participants were randomized to control (medication only) or treatment (medication plus exercise training) groups. Both underwent SMWT and echocardiography at baseline and after 12 weeks. Standardized exercise was monitored by healthcare experts. Result : This study compared 12 non-vasoreactive PH patients receiving standard therapy to 12 undergoing exercise training. The treatment group showed a significant mPAP decrease (66.8 to 63.4 mmHg, p=0.006), while the control group's reduction was non-significant (53.1 to 51.7 mmHg, p=0.061). Both groups improved 6MWT distances significantly after 12 weeks from 306.5 ± 72.7 meters to 318.3 ± 74.0 meters in the control group (p=0.041) and from 363.8 ± 63.6 meters to 382.9 ± 64.7 meters in the treatment group (p=0.000). No significant correlation was found between mPAP decrease and 6MWT increase in either group Conclusion : This study demonstrates improvements in mPAP and functional capacity following exercise training as an adjunctive therapy. However, no correlation was observed between the enhancement in functional capacity and the reduction in mPAP.